Strongyloides stercoralis Hyperinfection and Concomitant Cytomegalovirus Gastroenteritis in an Immunocompromised Host. Issue 7 (July 2019) - Crowe, Brooks R.; Duenas, Sean M.; Serrano, Antonio; Kingsbery, Joseph; Williams, Renee
Abstract : ABSTRACT: Strongyloides stercoralis infection typically presents with nonspecific gastrointestinal symptoms and no definitive or pathognomonic endoscopic findings. Disease burden can vary depending on a patient's immune status. Immunocompromised patients with strongyloidiasis can develop tremendous disease burden, extraintestinal dissemination, and are at risk for coinfection with other organisms. We present the case of an immunocompromised patient presenting with multiple gastrointestinal complaints found to have S. stercoralis hyperinfection and concomitant cytomegalovirus gastroenteritis.